Cognitive dysfunction, social participation, and performance of activities of daily living among a sub-urban community-dwelling older adults in Nigeria - Obiekwe Sochima Johnmark; Uzoamaka Nwakego Akobundu; Okwudili Precious Emuka; Akosile Christopher Olusanjo; Uchechukwu Martha Chukwuemeka; Ukamaka Gloria Mgbeojedo; Uchenna Prosper Okonkwo (Cogent Gerontology)
Cognitive dysfunction (CF) in older adults significantly impacts activities of daily living (ADLs), social participation (SP), instrumental activities of daily living (IADLs), and overall quality of life. This cross-sectional study assessed CF, SP, ADLs, and IADLs among 150 community-dwelling older adults (mean age 76.31 ± 8.74 years) in Nnewi, Nigeria. Data were collected using the Mini-Mental State Exam, Katz Index of Independence in ADLs, Lawton IADL scale, and Participation Scale. Mean scores for the IADL scale, Katz Index, SP, and CF were 6.03 ± 2.020, 5.73 ± 1.016, 7.47 ± 8.092, and 25.34 ± 5.800, respectively. Cognitive dysfunction prevalence was 29.3%. Most participants (83.3%) had no significant community or social function restrictions. Half required assistance with IADLs, but 93.3% were fully functional with basic ADLs. Significant relationships were found between ADLs and IADLs (p < 0.001), SP (p < 0.001), and CF (p = 0.001), and between IADLs, SP (p < 0.001), and CF (p = 0.001). Regular cognitive and social engagement programs are recommended to maintain functional abilities in older adults.